Do temperature and population size structure influence the quantity of fish eDNA in water? - Hervé, Alix; Domaizon, Isabelle; Baudoin, Jean-Marc; Dejean, Tony; Gibert, Pierre; Valentini, Alice; Logez, Maxime (Frontiers in Environmental Science, 2023)
Various factors can influence the concentration of eDNA found in the environment and blur the link between eDNA results and in situ fish abundances, biomasses or even occurrences. We studied the influence of one abiotic factor, the temperature, and one biotic factor, the fish size class, on the amount of fish eDNA detectable in water. To do so, we conducted two controlled experiments using tench (Tinca tinca, L) placed into outdoor mesocosms during 1 week. The quantification of fish eDNA abundances was performed using quantitative PCR after filtrating a large volume of water (30 L). The Bayesian hierarchical ANOVAs performed on qPCR results did not detect the effect of size class on eDNA amount, but fish eDNA concentration was shown to increase significantly when temperature rose by 6°C (no effect detected at 3°C). This suggests that fish assemblage quantification of two thermally contrasting sites through eDNA is not directly comparable.